Does Banking Digitalization Enhance Profitability and Efficiency? Evidence from Islamic Banks in Indonesia - Delavilanda Baby Efa (UIN Raden Mas Said Surakarta, 2026)
This study investigates the impact of banking digitalization on the financial performance of Islamic banks in Indonesia, with a particular focus on profitability and operational efficiency. Using panel data from 2020 to 2024 and applying a Fixed Effect Model (FEM), digitalization is proxied by the logarithm of total mobile banking transactions, while performance is measured by Return on Assets (ROA) and the Operating Expenses to Operating Income ratio (BOPO). The results demonstrate that banking digitalization exerts a significant dual effect on performance by increasing profitability and simultaneously reducing operational inefficiency. These findings indicate that digital transformation enhances both revenue generation and cost efficiency through process automation and reduced dependence on physical banking infrastructure. Among the control variables, bank size positively affects profitability, whereas the financing to deposit ratio (FDR) increases inefficiency, while capital adequacy ratio (CAR) shows no significant effect. The findings support the Resource-Based View (RBV), highlighting digital capability as a key strategic resource in improving bank performance. This study contributes to the literature by providing robust empirical evidence on the dual role of digitalization in enhancing both profitability and efficiency in Islamic banking, particularly in emerging markets, and offers important implications for strengthening digital transformation strategies. Keywords: Banking Digitalization; Profitability; Operational Efficiency; Islamic Banking